2001
DOI: 10.1063/1.1381531
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of laser-induced desorption–ionization of organic compounds from etched silicon and carbon surfaces

Abstract: The laser-induced desorption/ionization of organic compounds from etched carbon and silicon substrate surfaces was investigated. Two different etching procedures were used. Silicon surfaces were etched either by galvanostatic anodization to produce porous silicon or by a hyperthermal (∼5 eV) F-atom beam to produce nonporous silicon. Atomic force microscopy (AFM) images showed that both etching procedures yielded surfaces with sub-micrometer structures. Highly oriented pyrolytic graphite was etched with hyperth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
170
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 29 publications
7
170
0
1
Order By: Relevance
“…In MALDI, the [M ϩ 1]/M peak ratio was shown to vary from 34% to 123%, depending on matrix-to-analyte ratios [17]. Such fragment intensities may also depend on the micro-structure of the fractured surface [18] and the primary ion properties [19,20]. The cationic dye fragment possesses a nonlocalized charge due to resonance forms of methylene blue with a positively charged S and a positively charged quaternary ammonium group.…”
Section: Resultsmentioning
confidence: 99%
“…In MALDI, the [M ϩ 1]/M peak ratio was shown to vary from 34% to 123%, depending on matrix-to-analyte ratios [17]. Such fragment intensities may also depend on the micro-structure of the fractured surface [18] and the primary ion properties [19,20]. The cationic dye fragment possesses a nonlocalized charge due to resonance forms of methylene blue with a positively charged S and a positively charged quaternary ammonium group.…”
Section: Resultsmentioning
confidence: 99%
“…The previous findings on the aqueous-phase basicity of an analyte contributing more to ionization than the gasphase basicity of the same analyte suggested that proton transferring probably occurred in the condensed phase [6]. Consequently, this investigation focused on protonation between the analyte and its surrounding molecules in the condensed phase, including proton exchange with (1) the solvent where the analytes were dissolved in, (2) the solid surface where they were deposited on, and (3) other chemical species coadsorbed on the surface.…”
Section: Resultsmentioning
confidence: 86%
“…Sunner et al suggested that the ionization mechanism of DIOS is similar to surface-assisted laser desorption/ionization (SALDI), and the formation of gas-phase ions was initiated on the surface of sharp crystal tips and edges that protrude out of the sample surface. 43,44 On the other hand, many researchers suggested that the secondary ion-molecule reactions in the plume are essential to understanding the MALDI ionization process. 7,9,11 The ionization mechanism of DIOS may differ much from that of MALDI.…”
Section: Resultsmentioning
confidence: 99%